Detection and characterization of a MERS-related coronavirus (Betacoronavirus cameli) in velvety free-tailed bats (Molossus molossus, Mammalia) captured in Southern Brazil - Alexandre Sita; Micheli Filippi; Juliana Comerlato; Gabriela Espindola Birlem; Deivid de Souza da Silva; Larissa Mallmann; Vyctoria Malahyka de Abreu Góes Pereira; Meriane Demoliner; Juliana Schons Gularte; Alana Witt Hansen; Fernando Rosado Spilki; Matheus Nunes Weber (Brazilian Journal of Microbiology, 2026)
Bat-borne coronaviruses are of increasing interest due to their potential for zoonotic spillover, particularly within the Betacoronavirus genus. Partial genomic sequences related to MERS-like CoV was identified in multiple hosts, including humans, camelids, and bats from the families Vespertilionidae and Molossidae. In this study, we investigated the presence of coronaviruses in 65 Molossus molossus bats captured in southern Brazil using nested RT-PCR and high-throughput sequencing (HTS). One individual (1.5%) tested positive in a rectal swab, and sequence analysis revealed the presence of a MERS-related coronavirus ( Betacoronavirus cameli ). Phylogenetic reconstruction based on five genomic contigs clustered the virus within the Merbecovirus subgenus, confirming its close relationship to MERS-CoV strains previously detected in bats and dromedary camels. M. molossus is a widely distributed, insectivorous bat species with synanthropic behavior, commonly roosting in urban areas and human dwellings. The detection of a MERSr-CoV in this species in southern Brazil expands the known host range of these viruses and suggests that members of the Molossidae family may serve as reservoirs. These findings underscore the importance of continuous genomic surveillance in Neotropical bats, particularly in the context of environmental changes that intensify contact between wildlife, humans, and domestic animals.

Physiological and Proteomic Shifts in Pfaffia glomerata Under Drought and Elevated CO₂ - Tatiane Dulcineia Silva; Evandro Alexandre Fortini; Diego Silva Batista; Kerly Jessenia Moncaleano Robledo; Mariana Machado; Sérgio Heitor Sousa Felipe; Tadeu dos Reis de Oliveira; Moab Torres de Andrade; Letícia Monteiro Farias; Claudete Santa-Catarina; Vanildo Silveira; Philipp Westhoff; et al. (Journal of Plant Growth Regulation, 2026)
Drought is a major constraint to plant growth and productivity, and rising atmospheric CO₂ concentrations are expected to modify plant responses to water limitation. However, how CO₂ enrichment reshapes the physiological, metabolic, and molecular regulation of specialized metabolite production under drought remains poorly understood. Here, we investigated the combined effects of elevated CO₂ (e[CO₂]) and drought on plant morphophysiology and on the production of 20-hydroxyecdysone (20E), a phytoecdysteroid of therapeutic relevance whose accumulation may be influenced by environmental stress, in Pfaffia glomerata . Plants were grown under ambient (± 400 µmol mol⁻ 1 ; a[CO₂]) or elevated (± 800 µmol mol⁻ 1 ; e[CO₂]) CO₂ concentrations combined with sufficient or limited water supply. Elevated CO₂ promoted a metabolic shift under drought, characterized by increased investment in osmoregulatory compounds, including soluble sugars, myo-inositol, and glutamate. In contrast, drought reduced photosynthetic pigments and several primary metabolites regardless of CO₂ level. Drought induced the expression of lignin biosynthesis genes ( PgC4H , PgCCoAOMT , and PgCAD ) under both CO₂ conditions; however, PgCCR was specifically upregulated under e[CO₂] combined with drought, with consistently higher transcript levels than under ambient CO₂. Proteomic analyses revealed that e[CO₂] attenuated the accumulation of many canonical drought-responsive proteins, while selectively promoting the accumulation of the cytochrome P450 CYP72A219-like protein, which was associated with increased whole-plant 20E production. Together, these findings show that drought drives 20E biosynthesis, while elevated CO₂ modulates drought response intensity and allocation, ultimately affecting total 20E yield per plant and its relevance under future climate scenarios.

Genotoxic and cytotoxic effects of dietary patterns and lifestyle factors: A cross-sectional comparison of Brazilian and Spanish gym users - Diene da Silva Schlickmann; Gabriela Cristina Uebel; Patrícia Molz; Nikolas Mateus Pereira de Souza; Renato Alberto Weber Colombelli; Aline Alves da Luz; Munithele Moraes Eisenhardt; Geovana Andrine Vogt; Caroline Brand; Eliane Aparecida de Castro; Pedro J. Benito; Alexandre Rieger; et al. (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2026)

Screening for Viruses in Pallas’s Long-Tongued Bats (Glossophaga soricina) in Brazil - Alexandre Sita; Gabriela E. Birlem; Deivid S. da Silva; Larissa Mallmann; Meriane Demoliner; Mariana S. da Silva; Juliana S. Gularte; Vyctoria M. A. G. Pereira; Paula R. de Almeida; Alana W. Hansen; André A. Witt; Juliane D. Fleck; et al. (Journal of Molecular Evolution, 2025)

Identifying linear ultra-short peptides in Agrifood: Challenges and critical insights - Alexandre Weber; Barbara Deracinois; Benoit Cudennec; Maxime de Sousa Lopes Moreira; Rozenn Ravallec; Thierry Grard; Christophe Flahaut (Trends in Food Science & Technology, 2025)

Domestic cat hepadnavirus genotype B is present in Southern Brazil - Alaíse Tessmann; Juliana Sumienski; Alexandre Sita; Larissa Mallmann; Gabriela Espíndola Birlem; Nilson Júnior da Silva Nunes; Camila Gottlieb Lupion; Juliana Schaeffer Eckert; Meriane Demoliner; Juliana Schons Gularte; Paula Rodrigues de Almeida; Fernando Rosado Spilki; et al. (Virus Genes, 2025)

Detection of a novel hepacivirus in wild cavies (Cavia aperea aperea) - Gabriela Espíndola Birlem; Alexandre Sita; Juliana Schons Gularte; Deivid de Souza da Silva; Meriane Demoliner; Paula Rodrigues de Almeida; Juliane Deise Fleck; Fernando Rosado Spilki; Severino Silvano dos Santos Higino; Sergio Santos de Azevedo; Matheus Nunes Weber (Archives of Virology, 2025)

Evaluation of Mastadenovirus and Rotavirus Presence in Phyllostomid, Vespertilionid, and Molossid Bats Captured in Rio Grande do Sul, Southern Brazil - Alexandre Sita; Gabriela Espíndola Birlem; Deivid de Souza da Silva; Gabriela Mattos Possamai; Karla Petry; Paula Rodrigues de Almeida; Larissa Mallmann; Janaína Franciele Stein; Meriane Demoliner; Juliana Schons Gularte; Alana Witt Hansen; André Alberto Witt; et al. (Food and Environmental Virology, 2024)

The moderating role of macronutrient intake in relation to body composition and genotoxicity: A study with gym users - Diene da Silva Schlickmann; Patrícia Molz; Gabriela Cristina Uebel; Caroline Santos; Caroline Brand; Renato Alberto Weber Colombelli; Thalia Gama da Silva; Juliana Priebe Steffens; Eduarda da Silva Limberger Castilhos; Pedro J. Benito; Alexandre Rieger; Silvia Isabel Rech Franke (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2023)

Ancient origin and conserved gene function in terpene pheromone and defense evolution of stink bugs and hemipteran insects - Zarley Rebholz; Jason Lancaster; Hailey Larose; Ashot Khrimian; Katrin Luck; Michael E. Sparks; Kerry L. Gendreau; Leena Shewade; Tobias G. Köllner; Donald C. Weber; Dawn E. Gundersen-Rindal; Paul O'Maille; et al. (Insect Biochemistry and Molecular Biology, 2023)

Detection of human Mastadenovirus C in wild guinea pigs (Cavia aperea aperea) feces - Alexandre Sita; Gabriela E. Birlem; Paula R. de Almeida; Janaína F. Stein; Larissa Mallmann; Meriane Demoliner; Mariana S. da Silva; Juliana S. Gularte; Alana W. Hansen; Juliane D. Fleck; Fernando R. Spilki; Severino S. S. Higino; et al. (Brazilian Journal of Microbiology, 2022)

Foam-Assisted Water–Gas Flow Parameters: From Core-Flood Experiment to Uncertainty Quantification and Sensitivity Analysis - Andrés R. Valdez; Bernardo M. Rocha; Juliana Maria da Fonseca Façanha; Alexandre Vilela Oliveira de Souza; Aurora Pérez-Gramatges; Grigori Chapiro; Rodrigo Weber dos Santos (Transport in Porous Media, 2022)

Degradation of the micropollutant amoxicillin by photolysis and evaluation of the toxicity of byproducts generated in aquatic environments - Gabriela Vettorello; Daniel Kuhn; Aline Botassoli Dalcorso; Ani Caroline Weber; Bruna Costa; Sabrina Grando Cordeiro; Ytan Andreine Schweizer; Elisete Maria de Freitas; Alexandre Rieger; Clarice Steffens; Eduardo Miranda Ethur; Lucélia Hoehne (Sustainable Water Resources Management, 2022)

The Brazilian Cerrado is becoming hotter and drier - Gabriel S. Hofmann; Manoel F. Cardoso; Ruy J. V. Alves; Eliseu J. Weber; Alexandre A. Barbosa; Peter M. de Toledo; Francisco B. Pontual; Leandro de O. Salles; Heinrich Hasenack; José L. P. Cordeiro; Francisco E. Aquino; Luiz F. B. de Oliveira (Global Change Biology, 2021)
The Brazilian Cerrado is a global biodiversity hotspot with notoriously high rates of native vegetation suppression and wildfires over the past three decades. As a result, climate change can already be detected at both local and regional scales. In this study, we used three different approaches based on independent datasets to investigate possible changes in the daytime and nighttime temperature and air humidity between the peak of the dry season and the beginning of the rainy season in the Brazilian Cerrado. Additionally, we evaluated the tendency of dew point depression, considering it as a proxy to assess impacts on biodiversity. Monthly increases of 2.2−4.0℃ in the maximum temperatures and 2.4−2.8℃ in the minimum temperatures between 1961 and 2019 were recorded, supported by all analyzed datasets which included direct observations, remote sensing, and modeling data. The warming raised the vapor pressure deficit, and although we recorded an upward trend in absolute humidity, relative humidity has reduced by ~15%. If these tendencies are maintained, gradual air warming will make nightly cooling insufficient to reach the dew point in the early hours of the night. Therefore, it will progressively reduce both the amount and duration of nocturnal dewfall, which is the main source of water for numerous plants and animal species of the Brazilian Cerrado during the dry season. Through several examples, we hypothesize that these climate changes can have a high impact on biodiversity and potentially cause ecosystems to collapse. We emphasize that the effects of temperature and humidity on Cerrado ecosystems cannot be neglected and should be further explored from a land use perspective.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Recent chapters of Neotropical history overlooked in phylogeography: Shallow divergence explains phenotype and genotype uncoupling in Antilophia manakins - Fabio Raposo do Amaral; Marcos Maldonado‐Coelho; Alexandre Aleixo; Leilton W. Luna; Péricles Sena do Rêgo; Juliana Araripe; Thainara O. Souza; Weber A. G. Silva; Gregory Thom (Molecular Ecology, 2018)
Establishing links between phenotypic and genotypic variation is a central goal of evolutionary biology, as they might provide important insights into evolutionary processes shaping genetic and species diversity in nature. One of the more intriguing possibilities is when no genetic divergence is found to be associated with conspicuous phenotypic divergence. In that case, speciation theory predicts that phenotypic divergence may still occur in the presence of significant gene flow—thereby resulting in little genomic divergence—when genetic loci underpinning phenotypes are under strong divergent selection. However, a finding of phenotypic distinctiveness with weak or no population genetic structure may simply result from low statistical power to detect shallow genetic divergences when small data sets are used. Here, we used a subgenomic data set of 2,386 ultraconserved elements to explore genomewide divergence between two species of Antilophia manakins, which are phenotypically distinct yet evidently lack strong genetic differentiation according to previous studies based on a limited number of loci. Our results revealed clear population structure that matches the two phenotypes, supporting the idea that smaller data sets lacked the power to detect this recent divergence event (likely Cerrado populations. Besides their use in biogeography, subgenomic data sets may help redefine local conservation programmes by revealing cryptic population structure that may be key to population management.

ATLANTIC MAMMAL TRAITS : a data set of morphological traits of mammals in the Atlantic Forest of South America - Fernando Gonçalves; Ricardo S. Bovendorp; Gabrielle Beca; Carolina Bello; Raul Costa‐Pereira; Renata L. Muylaert; Raisa R. Rodarte; Nacho Villar; Rafael Souza; Maurício E. Graipel; Jorge J. Cherem; Deborah Faria; et al. (Ecology, 2018)
Measures of traits are the basis of functional biological diversity. Numerous works consider mean species‐level measures of traits while ignoring individual variance within species. However, there is a large amount of variation within species and it is increasingly apparent that it is important to consider trait variation not only between species, but also within species. Mammals are an interesting group for investigating trait‐based approaches because they play diverse and important ecological functions (e.g., pollination, seed dispersal, predation, grazing) that are correlated with functional traits. Here we compile a data set comprising morphological and life history information of 279 mammal species from 39,850 individuals of 388 populations ranging from −5.83 to −29.75 decimal degrees of latitude and −34.82 to −56.73 decimal degrees of longitude in the Atlantic forest of South America. We present trait information from 16,840 individuals of 181 species of non‐volant mammals (Rodentia, Didelphimorphia, Carnivora, Primates, Cingulata, Artiodactyla, Pilosa, Lagomorpha, Perissodactyla) and from 23,010 individuals of 98 species of volant mammals (Chiroptera). The traits reported include body mass, age, sex, reproductive stage, as well as the geographic coordinates of sampling for all taxa. Moreover, we gathered information on forearm length for bats and body length and tail length for rodents and marsupials. No copyright restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Selection strategy in families of energy cane based on biomass production and quality traits - Luís Cláudio Inácio da Silveira; Bruno Portela Brasileiro; Volmir Kist; Heroldo Weber; Edelclaiton Daros; Luiz Alexandre Peternelli; Márcio Henrique Pereira Barbosa (Euphytica, 2015)